2020
DOI: 10.1099/ijsem.0.004478
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces smaragdinus sp. nov., isolated from the gut of the fungus growing-termite Macrotermes natalensis

Abstract: The taxonomic position of a novel aerobic, Gram-positive actinobacteria, designated strain RB5T, was determined using a polyphasic approach. The strain, isolated from the gut of the fungus-farming termite Macrotermes natalensis, showed morphological, physiological and chemotaxonomic properties typical of the genus Streptomyces . Based on 16S rRNA gene sequence analysis, the closest phylogenetic neighbour of RB5T was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Our addition of ARTS2 resulted in the identification of an additional 50 essential genes that pass the three-marker threshold, with one of those markers being close proximity to an identified BGC. This remarkable finding speaks for the high potential to identify not only new bacterial diversity ( 64 66 ) but also novel natural products. Further work on both gene expression and compound production within termite colonies as well as biochemical studies to characterize the underlying gene clusters and their products is needed to further elaborate the roles of Actinobacteria within the fungus-farming termite system.…”
Section: Discussionmentioning
confidence: 89%
“…Our addition of ARTS2 resulted in the identification of an additional 50 essential genes that pass the three-marker threshold, with one of those markers being close proximity to an identified BGC. This remarkable finding speaks for the high potential to identify not only new bacterial diversity ( 64 66 ) but also novel natural products. Further work on both gene expression and compound production within termite colonies as well as biochemical studies to characterize the underlying gene clusters and their products is needed to further elaborate the roles of Actinobacteria within the fungus-farming termite system.…”
Section: Discussionmentioning
confidence: 89%
“…Based on 16S rRNA sequence analysis, seven strains were predicted to be potential novel actinomycetes ( Supplementary Table 1 ). Recently, a number of new actinomycetes have been isolated and identified from the worker gut of M. natalensis ( Benndorf et al, 2020a , b ; Schwitalla et al, 2020 ). The intestinal microflora of fungus-growing termite represents a promising resource of novel actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…They are beneficial for the insect microbiome because they influence the production of metabolites and the biosynthetic potential to inhibit and resist pathogens [99]. The main areas of insects that studies generally focus on are the intestinal region [100,101], the cuticle [102], and the head region [93,[103][104][105][106] (Table 3). Studies have shown that Streptomycetes live in symbiosis with insects and strengthen their defensive mechanism by producing chemicals for ecological adaptation [99].…”
Section: Symbiontsmentioning
confidence: 99%